2005
DOI: 10.1243/17403499jnn38
|View full text |Cite
|
Sign up to set email alerts
|

Screening Libraries of Circularly Permuted Proteins by Phage Display to Manipulate Protein Topographies

Abstract: Active biomolecules, particularly proteins, are increasingly used in functional nanostructures. For some applications, native proteins (i.e. proteins as they occur in nature) are not effective nanodevice components because distances between the ends of the protein and some protein functional domain exceeds some critical nanoscale distance. This problem occurs in sensing architectures that detect energy or electron transfer where native protein sizes exceed critical distances for quantum energy transfer or exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The results obtained showed that the relative eluate yield/output of binding phage particles was increased approximately 1000-fold and 100-fold from the first to the fourth round of affinity selection for libraries J (4 × 10 6 – 5 × 10 9 ) and I (1.1 × 10 6 – 3.5 × 10 8 ), respectively. During successful biopanning experiments, phage yields increase from one round to another round of selection enrichment (Eteshola et al, 2005; Eteshola et al, 2006). The results clearly indicates that isolation and enrichment of MIG binding phages was accomplished.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained showed that the relative eluate yield/output of binding phage particles was increased approximately 1000-fold and 100-fold from the first to the fourth round of affinity selection for libraries J (4 × 10 6 – 5 × 10 9 ) and I (1.1 × 10 6 – 3.5 × 10 8 ), respectively. During successful biopanning experiments, phage yields increase from one round to another round of selection enrichment (Eteshola et al, 2005; Eteshola et al, 2006). The results clearly indicates that isolation and enrichment of MIG binding phages was accomplished.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, we isolated affinity peptides recognizing thermally grown silica (Eteshola et al 2005) that can be inserted at various positions within receptor sequences as protein fusions to derive receptors that bind silica in specific orientation determined by the position of peptide insertion. Secondly, we developed a high-throughput method to modify the topography of receptor proteins (scanning circular permutagenesis; Eteshola et al 2006). When used in conjunction with a chemoselective conjugation method to deploy proteins on surfaces, different permuted variants of a single receptor hold analyte at different distances from the sensing surface.…”
Section: Resultsmentioning
confidence: 99%
“…In a second approach, we apply a technology we developed (scanning circular permutation or SCP of proteins; Eteshola et al 2006) in combination with chemoselective conjugation. The method allows alteration of protein topography so as to manipulate the position of the ends of the protein and any point on the protein surface (such as the antigen-combining site).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation